2006
DOI: 10.1037/0278-7393.32.4.716
|View full text |Cite
|
Sign up to set email alerts
|

Repetition learning in the immediate serial recall of visual and auditory materials.

Abstract: In five experiments a Hebb repetition effect, that is, improved immediate serial recall of an (unannounced) repeating list, was demonstrated in the immediate serial recall of visual materials, even when use of phonological STM was blocked by concurrent articulation. The learning of a repeatedly presented letter-list in one modality (auditory or visual) did not transfer to give improved performance on the same list in the other modality. This result was not replicated for word lists, however, for which asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(126 citation statements)
references
References 53 publications
8
113
5
Order By: Relevance
“…We replicated the Hebb repetition effect by showing that recall performance increased over the course of the experiment for the repeated trials, but not for the non repeated trials (see, e.g., Couture & Tremblay, 2006;Hebb, 1961;Page, Cumming, Norris, Hitch, & McNeil, 2006;Turcotte et al, 2005). This pattern of performance was similar for both aware and unaware participants, confirming that learning, as assessed through the immediate recall of the repeated sequence, is not modulated by awareness (see, e.g., Couture & Tremblay, 2006;McKelvie, 1987).…”
Section: Discussionmentioning
confidence: 62%
“…We replicated the Hebb repetition effect by showing that recall performance increased over the course of the experiment for the repeated trials, but not for the non repeated trials (see, e.g., Couture & Tremblay, 2006;Hebb, 1961;Page, Cumming, Norris, Hitch, & McNeil, 2006;Turcotte et al, 2005). This pattern of performance was similar for both aware and unaware participants, confirming that learning, as assessed through the immediate recall of the repeated sequence, is not modulated by awareness (see, e.g., Couture & Tremblay, 2006;McKelvie, 1987).…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, there is an element of the Hebb repetition learning that seems to be domain general, given that even spatial Hebb repetition learning correlated with non-word pairedassociate learning. As we have noted in more detail elsewhere (Page et al 2006), the existence of a spatial Hebb effect does not in any way weaken the hypothesized relation between a phonological Hebb effect and PWFL. Importantly, in Mosse and Jarrold's data, correlations with performance on the non-word paired-associate task were separably reliable for both domain-general Hebb repetition learning and domain-specific performance on the ISR task itself.…”
Section: The Hebb Repetition Effectmentioning
confidence: 70%
“…There is good evidence (Page et al 2006;Mosse & Jarrold 2008) that Hebb repetition learning is observable in many domains (e.g. phonological, spatial, visual).…”
Section: A Unified Model Of Immediate Serial Recall Hebb Repetition mentioning
confidence: 99%
“…Memory for order is thus critical for performance in this task and it seems that, at least partly, similar orderlearning mechanisms underlie performance in the Hebb repetition task and the SRT tasks (Page et al, 2006). In line with the SOLID hypothesis, a majority of studies using the SRT paradigm have reported impaired implicit-sequence-learning abilities in individuals with dyslexia (see Lum et al, 2013 for a recent meta-analysis and Pavlidou et al, 2010, for converging evidence in artificial grammar learning).…”
Section: Dyslexia As a Dis-order?mentioning
confidence: 87%